A novel quantitative immunoassay system for p53 using antibodies selected for optimum designation of p53 status. Issue 2 (February 1997) - Thomas, M D; McIntosh, G G; Anderson, J J; McKenna, D M; Parr, A H; Johnstone, R; Lennard, T W; Horne, C H; Angus, B
Abstract : AIM: To develop a highly sensitive and specific enzyme linked immunosorbent assay (ELISA) system for analysis of p53 protein in cancer lysates. METHODS: The anti-p53 monoclonal antibodies DO7, 1801, BP53.12, and 421, and anti-p53 polyclonal antiserum CM1 were assessed by immunohistochemistry and western blot analysis to identify those most suitable for determining p53 status of cancer cells. Antibodies with desired characteristics were used to develop a non-competitive sandwich type ELISA system for analysis of p53 expression in cancer cytosols. Using the ELISA, p53 protein concentrations were measured in a small series of breast cancers, and the quantitative values compared with p53 immunohistochemical data of the same cancers. RESULTS: DO7 and 1801 gave the most specific and reliable results on immunohistochemistry and western blot analysis. Using these two antibodies, a non-competitive sandwich type ELISA system was developed to analyse p53 quantitatively. Analysis of the breast cancer series showed a good correlation between immunohistochemistry and the ELISA-tumours were generally positive using both techniques. Discrepancies were noted however: some cancers were immunohistochemically negative but ELISA positive. One explanation for this may be that the ELISA is more sensitive than immunohistochemistry. CONCLUSION: The p53 ELISA system is a non-competitive double monoclonal antibody sandwich method, using DO7 and 1801 which have been shown to be highly specific for p53 protein by immunohistochemistry and western blot analysis. The lower threshold of the assay is 0.1 ng/ml analyte in an enriched recombinant p53 preparation. As p53 is now regarded as a protein associated with prognosis in breast and other cancers, the assay may have clinical applications.